Miscibility Analysis of Ethanol-Diesel Blends with Additives: A Comprehensive Investigation - Patel, Amit M.; Shah, Ronakkumar R.; Patel, Vijay K.; Sonawane, Chandrakant (Engineering, Technology & Applied Science Research, 2024)
Diesel-Ethanol (DE) blends have gained attention as an alternative fuel due to their potential to reduce emissions and improve the performance of diesel engines. However, a significant challenge when dealing with DE blends is that of phase separation. Achieving optimal miscibility between ethanol and diesel often requires the addition of additives. This research article thoroughly examines the miscibility, blend stability, and phase separation of DE mixtures with various additives. To prepare blends for the miscibility analysis, DE blends with 10%, 15%, and 20% ethanol were mixed with selected additives (n-pentanol, n-butanol, ethyl acetate, and diethyl ether) at a 2% concentration in each blend. Prior to the miscibility analysis, all blends were mixed using a magnetic stirrer and a probe ultrasonicator. The results indicated that DE10 with 2% n-propanol, DE10 with 2% n-butanol, DE15 with 2% n-butanol, and DE10 with 2% diethyl ether exhibited good miscibility without phase separation or sedimentation after four weeks. However, it was noted that all the other blends with higher ethanol content were eventually phase-separated after four weeks.